2009
DOI: 10.1246/cl.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Fe–O2 and the Fe=O Heme Species for Indoleamine 2,3-Dioxygenase during Catalytic Turnover

Abstract: Resonance Raman spectroscopy has been applied to two distinct temporal species of indoleamine 2,3-dioxygenase during catalytic turnover. We have identified two oxygen-isotopesensitive Raman modes at 569 and 798 cm ¹1 for the two respective species. The O analysis of the 798 cm ¹1 band indicates the existence of a ferryl-oxo heme, which is inconsistent with the previously proposed reaction mechanism. The present study thus provides a physical basis for the structures of the possible reaction intermediates.Indol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 17 publications
6
45
0
Order By: Relevance
“…Although Shimizu et al (27) noted in passing that IDO exhibits a peroxidase activity, no further consideration of the interaction of IDO with peroxide was reported until Poljak et al (54) demonstrated that exposure of IDO to hydrogen peroxide (Ն10 M) decreases the dioxygenase activity of the enzyme and oxidizes up to five of the eight Cys residues to sulfinic or sulfonic acid to result in changes to the structure of the enzyme. Following the detection of ferryl heme intermediates by resonance Raman spectroscopy during turnover of IDO (63,85,86), Lu and Yeh (87) The docking simulations conducted in this study suggest that binding of NADH at the active site of IDO is possible, and the ability to elute IDO bound to Cibacron blue affinity resin with either NADH or L-Trp is consistent with such interaction (88,89). Nevertheless, we were unable to detect any change in the electronic absorption spectrum of IDOFe 3ϩ or in the fluorescence emission spectrum of NADH upon mixing these two components anaerobically, so no simple means of quantifying or even verifying the affinity of the distal side of the heme cavity for NADH is available.…”
Section: Discussionmentioning
confidence: 99%
“…Although Shimizu et al (27) noted in passing that IDO exhibits a peroxidase activity, no further consideration of the interaction of IDO with peroxide was reported until Poljak et al (54) demonstrated that exposure of IDO to hydrogen peroxide (Ն10 M) decreases the dioxygenase activity of the enzyme and oxidizes up to five of the eight Cys residues to sulfinic or sulfonic acid to result in changes to the structure of the enzyme. Following the detection of ferryl heme intermediates by resonance Raman spectroscopy during turnover of IDO (63,85,86), Lu and Yeh (87) The docking simulations conducted in this study suggest that binding of NADH at the active site of IDO is possible, and the ability to elute IDO bound to Cibacron blue affinity resin with either NADH or L-Trp is consistent with such interaction (88,89). Nevertheless, we were unable to detect any change in the electronic absorption spectrum of IDOFe 3ϩ or in the fluorescence emission spectrum of NADH upon mixing these two components anaerobically, so no simple means of quantifying or even verifying the affinity of the distal side of the heme cavity for NADH is available.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the 2 / 3 modes shift to 1579/1503 cm Ϫ1 (with the intensity of the 3 mode considerably enhanced), the 8 mode shifts to 332 cm Ϫ1 , and the ␦ vinyl mode splits into two bands at 423 and 433 cm Ϫ1 . In addition, various in-plane asymmetric modes and outof-plane modes are activated, indicating that L-Trp binding to the ferryl species causes the reduction of the in-plane symmetry, thereby introducing out-of-plane distortion of the porphyrin macrocycle of the heme (29,49 Orelated modes, respectively. Intriguingly, the substrate-free spectrum shows two positive peaks at 786 and 810 cm Ϫ1 , in conjunction with a single negative peak at 752 cm Ϫ1 (Fig.…”
Section: Affinity Of the Ferryl Species Toward L-trp-mentioning
confidence: 99%
“…This band was identified for the ferric cyanide complex but was not identified when the enzyme is in the reduced state (15). It is also seen for the ferryl-oxo intermediate and the oxygenated intermediate in the presence of L-Trp (330-332 cm -1 ) (34) but not for the oxygenated intermediate in the absence of L-Trp (11). Thus, the band at 328 cm -1 could serve as a marker for the structure of the Fe-ligand moiety when L-Trp is bound.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, one might consider that the ratelimiting step could be different as a result of the intramolecular reaction in IDO and could represent an electron transfer step between the reductant and the mediator or between the mediator and IDO. However, since both the oxygenated and the ferryl-oxo intermediates are detectable when the reaction is initiated using IDO reduced with Na 2 S 2 O 4 (11), it is natural to consider that the rate-limiting step of N-formylkynurenine formation is represented by the rate of decay of either the oxygenated intermediate or the ferryl-oxo intermediate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation